Adnexal torsion in third trimester of pregnancy. (29th October 2012) - Passarinho, Rita Marquez; Afonso, Énio; Reis, Luís; Santos Silva, Isabel
Abstract : The authors report an unusual case of adnexal torsion in a patient in the third trimester of pregnancy. A 32-year-old woman, gravida 1, para 0, in the 32nd week of gestation initially presented with clinical signs of acute appendicitis. On laparotomy, it was identified that a necrotic mass of the right adnexa and performed a unilateral salpingo-oophorectomy. The postoperative period was uneventful. In the 37th week of gestation, the labour was induced by fetal intrauterine growth restriction. She delivered vaginally, a healthy baby, with 2085 g and an Apgar score of 9 and 10 at the first and fifth minute, respectively.